EBOLA VIRUS DISEASE PREPAREDNESS IN COUNTRIES BORDERING DEMOCRATIC REPUBLIC OF CONGO: LESSONS FROM WEST AFRICAN OUTBREAK: Ebola Virus Disease Preparedness - Okoror, Lawrence; Kapona, Otridah; Mpanga, Kasonde; Tobin, Alice E; Asogun, Danny (African Journal of Infectious Diseases (AJID), 2020)
Background: Ebola virus disease ravaged three West African countries in the wake of 2014 which was seen as the deadliest Ebola Virus Disease outbreak in history. Several lessons were taken out of the West African outbreak as one of the major lessons taken out from the West African outbreak is lack of preparedness by countries in this region. Materials and Methods: This paper looked at the mistakes of the West African outbreak and reports how such mistakes were corrected in the current outbreak going on in the Democratic Republic of Congo (DRC). Preparedness efforts are currently taking place in countries bordering DRC which included quick detection and response to an eventual EVD event. Results: This paid off on several occasions when cases from DRC to Uganda were quickly detected and response was as quick as possible. Preparedness carried out in Countries bordering DRC included setting up of Rapid Response Team and training of these teams both at country and regional level. All members of the RRT were trained in all areas of readiness which included community engagement, laboratory, logistics, surveillance, case management, sample collection, packaging and shipment as well as Infection Prevention and Control. Conclusion: These trainings have led to readiness to an eventual EVD event. Countries now have the ability to respond quickly with better Emergency Operation Centre for EVD.